2012
DOI: 10.1371/journal.pone.0049112
|View full text |Cite
|
Sign up to set email alerts
|

GSK3beta-Mediated Drp1 Phosphorylation Induced Elongated Mitochondrial Morphology against Oxidative Stress

Abstract: Multiple phosphorylation sites of Drp1 have been characterized for their functional importance. However, the functional consequence of GSK3beta-mediated phosphorylation of Drp1 remains unclear. In this report, we pinpointed 11 Serine/Threonine sites spanning from residue 634∼736 of the GED domain and robustly confirmed Drp1 Ser693 as a novel GSK3beta phosphorylation site. Our results suggest that GSK3beta-mediated phosphorylation at Ser693 does cause a dramatic decrease of GTPase activity; in contrast, GSK3bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(103 citation statements)
references
References 41 publications
1
98
1
1
Order By: Relevance
“…Next, we tested other 2 Drp1 forms with described phosphorylatable residues mutated, Drp1-S579A (corresponding to human Drp1-Ser616; 23 ) and Drp1-S693A 24 and no protection against excitotoxicity-mediated mitochondrial fragmentation was observed (not shown). To test the possibility that ROCK phosphorylated Drp1 in a new, undescribed residue, we immunoprecipitated with a phosphor-Ser antibody followed by western blot with anti Drp1, but no changes were detected after the NMDA treatment (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we tested other 2 Drp1 forms with described phosphorylatable residues mutated, Drp1-S579A (corresponding to human Drp1-Ser616; 23 ) and Drp1-S693A 24 and no protection against excitotoxicity-mediated mitochondrial fragmentation was observed (not shown). To test the possibility that ROCK phosphorylated Drp1 in a new, undescribed residue, we immunoprecipitated with a phosphor-Ser antibody followed by western blot with anti Drp1, but no changes were detected after the NMDA treatment (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…However, NIRKO mice exhibit no changes in phosphorylation of Drp1 at serine residue 616, which stimulates mitochondrial fission, or serine residue 637, which inhibits fission. Recent work has shown that Drp1 can also be phosphorylated at Ser-693 by GSK3-beta (49), and GSK3-beta is a known downstream target of insulin receptor signaling, such that insulin induced phosphorylation of the enzyme reduces its activity. We have previously shown that NIRKO mice display increased GSK3-beta activity (17), but whether this affects Ser-693 phosphorylation of Drp1 and mitochondrial dynamics is unclear, because no antibodies specific to this site exist.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work demonstrated that GSK3β also binds to Drp1 and is involved in regulating mitochondrial morphology [7]. Drp1 is one of the dynamin-related proteins, a large protein with an amino-terminal GTPase domain, middle domain, insert B, and GTPase effector domain (GED) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation is an important regulator of Drp 1 activity. Interestingly, phosphorylation of Drp 1 at multiple serine residues has opposing functional and morphological effects [7,[10][11][12][13][14][15][16][17][18]. Drp1 S637 was first identified as a phosphorylation site for PKA and as a dephosphorylation site for calcineurin [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation